Fracture toughness and fractographic investigation of polybutylene terephthalate/thermoplastic polyurethane binary blends reinforced by multi-walled carbon nanotubes using essential work of fracture approach. (March 2022) - Chalabi Tehran, Ata; Heidari, Farshad; Chakherlou, Tajbakhsh Navid; Najjar, Reza
In this paper, fracture toughness evaluation of polybutylene terephthalate (PBT)/thermoplastic polyurethane (TPU) binary blends and PBT/TPU/carbon nanotubes (CNTs) ternary nanocomposites have been conducted using both Izod impact and quasi-static fracture tests. Essential work of fracture (EWF) approach is used to study the fracture properties in details. The results of EWF tests revealed an effective role of TPU and CNTs in toughening mechanism of binary blends and ternary nanocomposites. According to EWF results, both the crack resistance and plastic deformation energies promoted in all compounds as compared to neat PBT. Energy dissipation in the yielding and tearing stages determined by the energy partitioning method. The obtained results indicated that displacement up to the failure point increased by increasing the TPU content, while inclusion of CNTs reduced this quantity. The specific non-essential work of fractureβ w p, β y w p, y  , andβ t w p, t increased with increasing the TPU contents which is confirmed by load-displacement curves. Whereas, addition of CNTs reducedβ w p andβ y w p, y values as compared to reference binary blend, however, ternary nanocomposites still have higher values as compared to pure PBT. In contrast with EWF results, high strain rate of impact test prevents the activation of toughness improving mechanisms that readily occurs in quasi-static loading.